Secang (Caesalpinia sappan L.) Heartwood Ethanolic Extract Shows Activity as Doxorubicin Co-chemotherapeutic Agent by Apoptosis Induction on T47D Breast Cancer Cells - Nurzijah, Ika; Putri, Dyaningtyas Dewi Pamungkas; Rivanti, Erlina; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2012)
Doxorubicin, primary chemoteurapeutic agent used for breast cancer treatment, is known to have various side effects included multi drug resistance 9MDR) phenomenon. Therefore, exploration of co-chemotherapeutic agent is important to be conducted in order to prevent MDR. Secang (Caesalpinia sappan L.) which contains active compounds brazilin and brazilein, is proven to have activity as anticancer. The aim of this study is to determine the potency of Caesalpinia sappan L.ethanolic extract (CEE) as co-chemotherapeutic agent of doxorubicin and its mechanism through apoptosis induction on T47D breast cancer cells. Caesalpinia sappan L. heartwood powder was macerated with ethanol 70%. The cytotoxic effect of CEE alone and its combination with doxorubicin was analyzed using MTT assay. Apoptosis assay was done by flowcytometry-annexin V method. CEE showed cytotoxic activity on T47D cells with IC50 value of 35 μg/ml, while combinatorial test showed that all of combination doses of CEE and doxorubicin gave synergistic effect. Flowcytometry-annexin V assay proved that treatment of CEE induced apoptosis of doxorubicin. Based on these results, we conclude that Caesalpinia sappan L. heartwood ethanolic extract is potential to be developed as co-chemotherapeutic agent of doxorubicin.Keywords : Caesalpinia sappan L., doxorubicib, apoptosis, T47D cells.